2017
DOI: 10.1002/cncy.21823
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cytology—nuclear versus architectural atypia within the “Atypia of undetermined significance/follicular lesion of undetermined significance” Bethesda category have significantly different rates of malignancy

Abstract: The disparity between malignancy risks within the Bethesda "atypical" category suggests that cytologic (nuclear) atypia is significantly more predictive of malignancy than architectural atypia. This supports the substratification of patients according to risk and a corresponding management approach within this category. A sonographic finding of irregular margins is also predictive for malignancy. Cancer Cytopathol 2017;125:245-256. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
50
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 57 publications
(210 reference statements)
10
50
2
Order By: Relevance
“…Nishino and Wang, compiling a series of retrospective studies, found malignancy in 55% of patients in subcategory NA versus 22% in subcategory AA. In subsequent studies, these rates were, respectively, 52.7% versus 6.8%, 51% versus 8.1%, 35% versus 10%, 65.8% versus 14.3%, and 36.8% versus 14.7% . To our knowledge, the only prospective study available showed malignancy in 41.3% of cases of subcategory NA and in 10.8% of subcategory AA …”
Section: Discussionmentioning
confidence: 82%
“…Nishino and Wang, compiling a series of retrospective studies, found malignancy in 55% of patients in subcategory NA versus 22% in subcategory AA. In subsequent studies, these rates were, respectively, 52.7% versus 6.8%, 51% versus 8.1%, 35% versus 10%, 65.8% versus 14.3%, and 36.8% versus 14.7% . To our knowledge, the only prospective study available showed malignancy in 41.3% of cases of subcategory NA and in 10.8% of subcategory AA …”
Section: Discussionmentioning
confidence: 82%
“…FNAs could be placed into this category for different cytologic characteristics ranging from limited nuclear atypia and focal architectural changes to Hürthle cells or even atypical lymphocytic aspirates . By subcategorizing AUS according to types of atypia, several studies have demonstrated differences in the ROM for better risk stratification . This approach has been adopted and is recommended by the new 2017 TBSRTC .…”
Section: Discussionmentioning
confidence: 99%
“…Gan et al from the National University Hospital in Singapore reported a series of 137 AUS nodules undergoing thyroidectomy. There were 37 malignant nodules, and 6 of them were FVPTC (5 as AUS‐N and 1 as AUS‐F).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations